(untitled) (Revista Contexto & Saúde, 2026)
Objective: To evaluate the infrastructure and organization of care provided to individuals with overweight and obesity (O/O) in Primary Health Care (PHC) in small, medium, and large municipalities in the state of Goiás. Methods: A cross-sectional study was conducted with professionals from 330 health units in Goiás, using an electronic questionnaire. A descriptive analysis was performed, and differences between municipalities were analyzed using the chi-square and Fisher’s exact tests, with Bonferroni correction for multiple comparisons. Results: Less than 41% of health units have basic infrastructure items, and only 52.4% conduct territorial mapping. The most common organizational strategies were referral protocols and risk stratification; however, less than 35% of professionals use Food and Nutrition Surveillance tools, indicating low integration of these practices into the work process. Small municipalities presented better structural conditions and greater community integration; medium-sized municipalities showed weaknesses in mapping and care organization; and large municipalities exhibited the most deficiencies, especially in infrastructure, problem-solving capacity, and data recording. Conclusion: PHC in Goiás presents significant limitations in infrastructure and care organization for the management of overweight and obesity, with poorer performance in large municipalities.